Temporalidade de Documentos Públicos - Trivellato, Regina Célia Franco; Santos, Patrícia Rosa Mendes dos; Zago, Mirian Barbosa; Bordin, Fábia Martins de Oliveira (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Regina Célia Franco Trivellato